2009
DOI: 10.1016/j.nucmedbio.2009.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography imaging of (2R,3R)-5-[18F]fluoroethoxybenzovesamicol in rat and monkey brain: a radioligand for the vesicular acetylcholine transporter

Abstract: Introduction The regional brain distribution of (2R,3R)-5-[ [18F]fluoroethoxy-benzovesamicol ((-)-[18F]FEOBV), a radioligand for the vesicular acetylcholine transporter (VAChT), was examined in vivo in mice, rats, and rhesus monkeys. Methods Regional brain distributions of (-)-[18F]FEOBV in mice were determined using ex vivo dissection. MicroPET imaging was used to determine the regional brain pharmacokinetics of the radioligand in rat and rhesus monkey brains. Results In all three species, clear heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 13 publications
4
45
0
Order By: Relevance
“…In addition, peripheral [ 18 F]FEOBV metabolism does not generate metabolites capable of crossing the blood-brain barrier (Landry St-Pierre et al, 2008b). [ 18 F]FEOBV is also stable in the brain and plasma, and does not generate significant amounts of free [ 18 F]fluoride in primates, as opposed to other vesamicol derivatives (Giboureau et al, NeuroImage 62 (2012) 555-561 2007; Kilbourn et al, 2009;Soucy et al, 2010). Despite slow in vitro kinetics (Mulholland et al, 1998), reversible kinetics of [ 18 F]FEOBV can be observed during a 60 min dynamic PET scan (Kilbourn et al, 2009;Landry St-Pierre et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, peripheral [ 18 F]FEOBV metabolism does not generate metabolites capable of crossing the blood-brain barrier (Landry St-Pierre et al, 2008b). [ 18 F]FEOBV is also stable in the brain and plasma, and does not generate significant amounts of free [ 18 F]fluoride in primates, as opposed to other vesamicol derivatives (Giboureau et al, NeuroImage 62 (2012) 555-561 2007; Kilbourn et al, 2009;Soucy et al, 2010). Despite slow in vitro kinetics (Mulholland et al, 1998), reversible kinetics of [ 18 F]FEOBV can be observed during a 60 min dynamic PET scan (Kilbourn et al, 2009;Landry St-Pierre et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 F]FEOBV is also stable in the brain and plasma, and does not generate significant amounts of free [ 18 F]fluoride in primates, as opposed to other vesamicol derivatives (Giboureau et al, NeuroImage 62 (2012) 555-561 2007; Kilbourn et al, 2009;Soucy et al, 2010). Despite slow in vitro kinetics (Mulholland et al, 1998), reversible kinetics of [ 18 F]FEOBV can be observed during a 60 min dynamic PET scan (Kilbourn et al, 2009;Landry St-Pierre et al, 2008a). This discrepancy between in vivo and in vitro kinetic speeds is a relatively common feature of PET radiopharmaceuticals, a notable example being [ 3 H]SCH 23390 (Gifford et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the idea of a ring fusion as made with benzovesamicols, structurally related compounds were developed. Two candidates of the class of morpholinovesamicols were 18 F-radiolabeled and studied in vivo in rats and pigs [29e31]. In particular, the 4-fluoro-benzoylated derivative [ 18 F] FBMV showed a typical accumulation in VAChT-containing brain regions and a significant reduction of cortical binding after a specific cholinergic lesion.…”
Section: Introductionmentioning
confidence: 99%
“…The development of microPET imaging applications has provided the ability to collect sensitive and quantitative three-dimensional molecular information from the living brains of a variety of animals including nonhuman primates (NHP) [12][13][14]. In order to obtain sufficient data from living animals and longitudinally assess the neurotoxic effects associated with developmental exposures to anesthesia, we have developed a microPET protocol thought to target neuronal damage in vivo using imaging approaches [15,16].…”
Section: Introductionmentioning
confidence: 99%